Accounting Conservatism and Incentives: Intertemporal Considerations - Glover, Jonathan C.; Lin, Haijin H. (The Accounting Review, 2018)
ABSTRACT We study intertemporal incentive properties of conditional accounting conservatism. Conservatism has detrimental and beneficial properties. In our first model, conservatism introduces downward bias in the first period; any understatement of first-period performance is reversed in the second period. A conservative bias is not costly in the first period but instead is costly in the second period when a new manager may be rewarded for the performance of his predecessor. In an extension on learning, we illustrate a beneficial role of conservatism in fine-tuning incentives. In the second model, conservatism is modeled as recognizing effort-independent bad news early and good news late. Recognizing bad news early can be optimal because of intertemporal rent shifting, which improves incentives via an “incentive spillback.” We also study overlapping projects (a multi-task setting) in which an interior accounting system can be optimal to avoid making one of the overlapping projects an incentive bottleneck. JEL Classifications: D21; D74; D82; D86.